Antiviral Therapy for Varicella Zoster Virus (VZV) and Herpes Simplex Virus (HSV)-Induced Anterior Uveitis: A Systematic Review and Meta-Analysis - Testi, Ilaria; Aggarwal, Kanika; Jaiswal, Nishant; Dahiya, Neha; Thng, Zheng Xian; Agarwal, Aniruddha; Ahuja, Alka; Duggal, Mona; Kankaria, Ankita; Ling Ho, Su; Chee, Soon-Paik; Westcott, Mark; et al. (Frontiers in Medicine, 2021)
Topic: Herpes simplex virus (HSV) and varicella zoster virus (VZV) are the most common ocular pathogens associated with infectious anterior uveitis. Currently, there are a number of antiviral agents administered to treat viral anterior uveitis (VAU). However, there is no consensus or guidelines about the most appropriate approach leading for the best treatment outcomes with fewer ocular complications. Clinical Relevance: To perform a systematic review and meta-analysis of the efficacy of different antiviral therapies in the management of anterior uveitis secondary to HSV and VZV. Methods: We searched PubMed, Web of Science, CINAHL, OVID, and Embase up to January 2020. Randomized trials, non-randomized intervention studies, controlled before and after studies and observational studies assessing the effect of oral and or topical treatments for VAU were considered. Data extraction and analysis with evaluation of the risk of bias in the included trials were performed. Results: Oral acyclovir demonstrated a statistically significant good treatment outcome in the management of VZV anterior uveitis (vs. placebo) (OR 0.26, 95% CI 0.11–0.59), but did not have similar effect in HSV anterior uveitis (OR 0.47, 95% CI 0.15–1.50). In the treatment of VZV anterior uveitis, there was significant superiority of oral acyclovir−7 day course—over topical acyclovir (OR 4.17, 95% CI 1.28–13.52). Whereas, there was no significant superiority of one of the following treatment regimens over the others: topical acyclovir over topical corticosteroids (OR 1.86, 95% CI 0.67–5.17), and oral acyclovir−7 day course—over oral acyclovir−14 day course—(OR 0.21, 95% CI 0.01–4.50) or oral valaciclovir (OR 1.40, 95% CI 0.48–4.07). Conclusion: Treatment of HSV and VZV anterior uveitis is currently based on individual experiences and limited literature, largely due to weak clinical trial evidence in this regard. Our results highlight the existence of a substantial gap in our evidence base. This finding might contribute to future research studies to ascertain the role of different antiviral therapies in the treatment of VAU. Systematic Review Registration: PROSPERO registration number: CRD420202 00404.